A Study of Stakeholder Perspectives of Enterprise Architecture Methodology (TOGAF Framework) - Yunita Yunita; Denada Fatimah Zahra; Ahsani Takwim (Kresnamedia Publisher, 2020)
Enterprise architecture is a method or explanation of how to plan, compile, structure, and realize company structures, business processes, information systems, and related infrastructure as well as an explanation of how to design systems that can support business needs and related technology to make vision and mission achieve results. targeted. The framework used in this research is TOGAF and FEAF. TOGAF has a detailed and comprehensive framework and has a methodology that supports its application but is invincible from a stakeholder point of view. The aim of this study is to develop two frameworks by comparing the differences that each Framework has from the perspective of stakeholders. The research methodology begins with a literature study and analysis with a comparison of the TOGAF and FEAF Frameworks. The results showed that. The final result of this research is the TOGAF framework with the components that are owned by FEAF from the perspective of the stakeholders so as to produce a TOGAF framework that suits the specific needs of the organization.